The Effect of Beatbox-Accompanied Storytelling on Receptive Language Development in Children Aged 4–5 Years - Abda Billah Faza Muhammadkan Bastian; Imroatun Imroatun; Muhiyatul Huliyah; Alinda Yunita; Juholillah Juholillah; Dind Ibra Benign Sajid (GENIUS: Indonesian Journal of Early Childhood Education, 2026)
This study examined the effect of beatbox-accompanied storytelling on receptive language development among early childhood learners. A one-group pretest–posttest pre-experimental design was employed involving 20 children aged 4–5 years from Wadas Kelir Creative House Playgroup (KB Rumah Kreatif Wadas Kelir), Purwokerto, Central Java. Children’s receptive language performance was assessed before and after participating in beatbox-integrated storytelling activities using an observation-based questionnaire. Data were analyzed through descriptive statistics, normality testing, paired-samples t-test, and regression analysis using SPSS. The findings showed a significant improvement in children’s receptive language scores after the implementation of beatbox-accompanied storytelling (p < .05). Regression analysis indicated that the storytelling intervention contributed to receptive language outcomes, explaining 27.9% of the variance (R² = .279). These findings suggest that integrating beatboxing into storytelling creates a multisensory and interactive learning experience that supports children’s attention, engagement, comprehension, and responses. This study highlights beatboxing as a creative pedagogical strategy for strengthening receptive language development in early childhood education.